2021
DOI: 10.1016/j.ensci.2021.100350
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies in chronic adhesive arachnoiditis - A case series and literature review

Abstract: Chronic spinal adhesive arachnoiditis (CSAA) is a rare condition with limited therapeutic options. Surgical treatment proves effective in approximately 60% of cases. Conservative treatment options have not been extensively investigated. Here, we report the course of the disease, analyze the effect of immune treatments in patients with CSAA who were treated in the University Hospital Essen between 2015 and 2020, and conduct a literature review. Three out of four patients showed no improvement after treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…9 In our patient, detethering was not deemed feasible because of the extent of cord tethering. Although systemic steroids can ameliorate symptoms, 10 our patient failed a course of pulsed methylprednisolone. Epidural steroids may increase the risk of adhesive arachnoiditis rather than representing a promising therapy.…”
Section: Sectionmentioning
confidence: 64%
See 1 more Smart Citation
“…9 In our patient, detethering was not deemed feasible because of the extent of cord tethering. Although systemic steroids can ameliorate symptoms, 10 our patient failed a course of pulsed methylprednisolone. Epidural steroids may increase the risk of adhesive arachnoiditis rather than representing a promising therapy.…”
Section: Sectionmentioning
confidence: 64%
“…Laboratory blood and CSF studies are nonspecific and mainly used to rule out other (e.g., infectious or autoimmune) causes of arachnoiditis. 10,13,14 MRI often shows arachnoid cysts, nerve root clumping or enhancement, cord swelling, and arachnoid septations. 8,15 Snake-eye cord appearance on imaging is nonspecific but may be prognostically unfavorable as it can represent cystic gray matter necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeries have been done depending on the symptoms and causative pathology. Procedures like expansive duraplasty, microscopic adhesiolysis, myelotomy, intraventricular drain placement, and spondylodesis have been tried [ 18 , 19 ]. However, the long-term outcome of surgical treatment in these cases is not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term outcome of surgical treatment in these cases is not satisfactory. Conservative management with corticosteroids has proven to be useful in the early stages of spinal arachnoiditis but not in the later stages [ 19 ]. In our case, we commenced intravenous steroids very early in the disease along with proper antibiotics, which helped in the timely resolution of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Medical treatment for arachnoiditis did not show improvement until now. Hackert et al [10] reported improvement in one fourth patient after immunotherapies including corticosteroids, methotrexate, or plasmapheresis but firm clues seem to insufficient. There are several surgical options to treat an arachnoid cyst with adhesive arachnoiditis.…”
Section: Discussionmentioning
confidence: 99%